(untitled) (Panacea Journal of Medical Sciences, 2025)
Background: Indwelling urethral catheter use is responsible for 70–80% of UTIs and is a major cause of sepsis. The research aims to investigate the prevalence, risk factors, and causative agents linked to urinary tract infections (UTIs) related to catheter use, along with understanding the antibiotic susceptibility patterns. Aim & Objective: To determine the microbiological profile and risk factors associated with Catheter Associated Urinary Tract Infections (CAUTI). Materials and Methods: A hospital-based cross-sectional study was conducted in the Department of Microbiology at a Tertiary care Hospital from August to December 2023, on 200 patients with indwelling catheters admitted in Intensive Care Unit. Urine samples were collected in an aseptic procedure and processed within a 2-hour timeframe. Uropathogen identification and Antibiotic Susceptibility Testing were done following CLSI guidelines 2023. Results: A total of 200 patients with indwelling urinary catheter with an aggregate of 1457 catheter days over a period of 5 months. 32 were culture positive in clinically suspected cases of CAUTI. The CAUTI rate was 21.96 per 1000 catheter days with predominant etiological agents as Non albicans Candida 14 (43.75%) followed by E.coli 8 (25%) and Candida albicans 5 (15.63%). Conclusion: This research offers foundational information on the rate of catheter-associated urinary tract infections (CAUTI), the predominant uropathogens, and associated risk factors within our institution.